A new species and two new records of the leafhopper genus Iassus Fabricius (Hemiptera: Auchenorrhyncha: Cicadellidae) from Korea, with a key to the Korean Iassus species - Kwon, Sua; Jung, Sunghoon (Zootaxa, 2017)
A new species, Iassus psudoulmi sp. nov. Kwon et Jung, and two new records, Iassus lateralis (Matsumura, 1905) and I. iziaslavi (Anufriev, 1977) from Korea are presented. Descriptions, illustrations of the species and a key to the Korean Iassus species are provided.